FAKTOR - FAKTOR YANG BERHUBUNGAN DENGAN TEKANAN DARAH PADA PEGAWAI NEGERI SIPIL SMA N 8 SEMARANG - Vilda Ana Veria Setyawati; Yekti Wirawanni (VISIKES: Jurnal Kesehatan Masyarakat, 2011)
Background: Obesity and dyslipidemia risk factors associated with increased blood pressure and hypertension. Obesity indicators which are associated with hypertension are percent body fat and waist circumference Lipid profile which are associated with hypertension are total blood cholesterol and triglycerides. There are limited studies concerning the association of percent body fat, waist circumference, total blood cholesterol, and triglycerides with systolic and diastolic blood pressure, mainly in Indonesian state employer.Methods: The subject of this cross sectional study consisted of 38 state employer of SMAN 8 Semarang who taken with simple random sampling. Data were collected including percent body fat, waist circumference, total blood cholesterol, triglycerides, systolic and diastolic blood pressure. Pearson Product moment and rank Spearman have been used for analysis association between variables with Ã¡ = 0,05. Multivariate analysis uses multiple regression.Result: There were no association between percent body fat, waist circumference, total blood cholesterol with systolic blood pressure and diastolic blood pressure (p > 0,05). But, there was association between triglycerides with systolic blood pressure (p = 0,017 ; r = 0,385) anddiastolic blood pressure (p = 0,027; r= 0,359). Just blood triglycerides which can be tested by multiple regression. Systolic blood pressure = 104,215 + 5,047.10-2 triglycerides. Diastolic blood pressure = 70,2 + 2,992.10-2 triglycerides.Key Words: Hypertension, percent body fat, waist circumference, total blood cholesterol, triglycerides.